Evaluation of the Effect of Lymph Node Status on the Survival of Non-Small Cell Lung Cancer Patients With Brain Metastases: Applications of a Novel Grade Prognostic Assessment Score Model Involving N Stage - Zhu, Jianfei; Wang, Wuping; Xu, Shuonan; Jia, Chenghui; Zhang, Qingqing; Xia, Yanmin; Wang, Wenchen; Wen, Miaomiao; Wang, Xuejiao; Wang, Hongtao; Zhang, Zhipei; Cai, Ling; et al. (Frontiers in Oncology, 2020)
Background Grade prognostic assessment (GPA) is widely used to evaluate the prognosis of non-small cell lung cancer (NSCLC) patients with brain metastases (BMs). This study aimed to investigate whether lymph node status (LNS) could be included as one of the GPA variables for NSCLC with BMs. Methods Overall, 586 patients with NSCLC and BMs were retrospectively analyzed. Overall survival stratified by LNS was analyzed using the Kaplan-Meier method. Multivariate analysis was also performed to identify independent prognostic factors using the Cox proportional hazards progression model. In the updated GPA index, prognostic factors and criteria of GPA score were weighted by effect magnitude relative risk (RR) and statistical significance. Results In NSCLC patients with BMs, those with lymph node involvement had worse overall survival (mOS, 13.4 months vs. 25.9 months, P <0.001) than those without lymph node involvement. Multivariate analysis showed that LNS might be an independent prognostic factor (RR: 1.702, CI: 1.340–2.162, P <0.001). Finally, five prognostic factors including LNS, the age of the patient, Karnofsky performance status (KPS), the number of BMs, and extracranial metastases were enrolled in our novel GPA index. With the updated GPA index involving the N stage, survival analysis was also performed. Prognostic results were significantly different among these four subgroups (Class A vs. Class B, P=0.047; Class B vs. Class C, P<0.001; Class C vs. Class D, P=0.007). Conclusions These results indicate that LNS might be an indispensable prognostic factor in NSCLC with BM. The novel GPA model involving the N stage could provide more reliable evidence to estimate the survival of NSCLC patients with BMs.